Developing a Management Model of Early Education Services for Children With Autism - Putranti, Alifiani Hikmah; Florentinus, Totok Sumaryanto; Sugiharto, Dwi Yuwono Puji; Herini, Elisabeth Siti (The Journal of Educational Development, 2019)
Early education services for children with autism are a place for early intervention for autistic children of pre-school age as a bridge to further education. Autism is a neurological development disorder under the age of 3 years with characteristics of communication and behavioral disorders. Pre-school age is a period of rapid brain development so early intervention or early education for children with autism is an attempt to reduce the manifestation of autism clinics. Development of early education service management for children with autism aims to intervene with autism from an early age in a comprehensive manner and in accordance with their growth and development. This study applies the Research and Development approach through four stages, namely (1) preliminary research, (2) model development, (3) validation, and (4) final model. Data were drawn using open and closed questionnaires and interviews in four early education service institutions for children with autism in Semarang. The data were processed using descriptive analysis, percentage, average, and qualitative analysis. The final model of early education service management for children with autism focuses on aspects of management which consist of (1) comprehensive planning based on the standard parameters by considering comorbidities and health status and (2) early education for children with autism carried out comprehensively and sustainably between teachers, parents, and medical personnel.